Culture in Indonesian English Language Teaching (ELT): A Critical Literature Review - Karmila Mokoginta (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2024)
This article aims to analyze the current situation of Indonesian ELT concerning the recommendation to integrate more cultural elements in ELT practices. To achieve the objective, some studies were critically reviewed to gain insights into Indonesian ELT researchers' latest trends and perspectives. The writer collected some articles related to the topic written in the last ten years and reviewed them using some steps of critical literature review. The results show that many efforts have been made to integrate Indonesian cultures into Indonesian ELT practices, especially in learning materials. However, there is a discrepancy between the growing concerns regarding the negative impacts of Western values through ELT classrooms and the preference among Indonesian students towards target and international cultures of English. More studies are needed to gain better perspectives.